Decision Delivery Interval for Emergency Caesarean Section and Associated Maternal and Neonatal Outcomes in a Tertiary Hospital in South- South Nigeria - Okpara, Abuchi Loveday; Orisabinone, Idowu; Aigere, E. O. Samuel; Ozori, Ebiogbo Stanley; Atemie, Gordon; Ogidigba, Peter Ikorira (British Journal of Healthcare and Medical Research, 2023)
Standard guidelines recommend that delivery by caesarean section should be initiated within 30 minutes of decision to operate to avoid adverse maternal and fetal outcome. Patient however encounter delays despite recommended time frames. The aim of the study was to determine the average decision delivery interval and its effect on perinatal outcomes in emergency caesarean sections. The study was a descriptive cross-sectional study. The study population consisted of 120 consecutive pregnant women who had emergency caesarean section who met the inclusion criteria. Data was collected using a structured questionnaire and analyzed with SPSS version 20. Sixty – two (51.7%) of the study participants were booked. The commonest indication for CS was cephalo-pelvic disproportion (35%). The mean DDI was 209.5± 98.9 minutes. Patient factor was the leading cause of delay due to lack of funds and non-provision of surgical materials (55%). Only delay in obtaining consent was statistically significant in prolonging DDI interval. Five-minute APGAR score was normal in 91.7%. Indication for emergency CS was significantly related to fetal outcomes; asphyxia and mortality. There was lack of association between DDI, perinatal and maternal outcome, which may indicate decision delivery interval of 30 minutes or less may not be applicable to all emergency CS, especially in developing countries with infrastructural challenges. However, decision- delivery interval should be considered as an important contributing factor for adverse neonatal outcomes. Therefore, clinical judgment is required to assess the urgency of caesarean section to prevent neonatal morbidity and mortality.